The burden and associated social determinants of mental health among adolescent girls and young women in Sub-Saharan Africa - Elsa Denise Perestrelo; Saikou Sanyang; Jinan Abi Jumaa (Discover Public Health)
Abstract Background Adolescent girls and young women (AGYW) are an important sub-group in Sub-Saharan Africa (SSA), where young people make up more than two-thirds of the population. AGYW face a considerably higher chance of experiencing mental health issues. This investigation aims to examine peer-reviewed literature on the mental health burden and associated social determinants of mental health among adolescent girls and young women (AGYW) aged 10–24 in Sub-Saharan Africa. Methods  Electronic databases such as CINAHL, PubMed, Science Direct, and Google Scholar were searched for peer-reviewed journals on mental health in adolescent girls and young women in SSA. A study must have been authored in English and published between 01 January 2015 and 31 December 2023 to satisfy the inclusion criteria. Results A total of 39 studies were analysed. The review’s findings revealed that the research on mental health in AGYW recognised several biological, demographic, social, economic, neighbourhood, and environmental elements shaping mental health outcomes in this population. Social determinants of mental health that are unique to or disproportionately affect AGYW such as pregnancy, HIV/AIDS and sexual violence present concerning associations with adverse mental health outcomes in different rural and urban settings. Conclusion The review's findings shed light on the multifaceted nature of mental health concerns, emphasising the significance of a focused strategy for addressing mental health in teenage girls and young women across the region. Recommendations include focusing on community-based interventions that address factors particular to the target population in resource-poor contexts and increasing attention to scaling up mental health research capability and policy implementation.